Position and Legal Consequences of Deed of Recognition of Illegitimate Children Made by a Notary - Riyanto, Syahvaldo (Sultan Agung Notary Law Review, 2023)
This research aims to analyze: 1) The legal position of deeds of recognition of illegitimate children made by Notaries. 2) Legal consequences of the deed of recognition of illegitimate children made by a Notary. This type of research is descriptive research. The approach method used in this research is the statutory approach. This type of research falls within the scope of normative legal research. The type and source of data in this research is secondary data. obtained by literature study. The analysis in this research is prescriptive. The results of the research concluded: 1) The legal position of the deed of recognition of illegitimate children made by a notary is that the notary's position as a public official is an honorable position given by the state attributively through law to someone who is trusted. Based on Article 281 of the Civil Code which states that recognition of illegitimate children can be done with an authentic deed, if it has not been contained in the birth certificate or at the time of the marriage. However, the legal position of the deed of recognition of illegitimate children made by a notary based on Article 281 of the Civil Code is ambiguous. after the publication of Presidential Regulation of the Republic of Indonesia Number 96 of 2018 concerning Requirements and Procedures for Population Registration, which in Article 51 states that the registration of recognition of children of residents in the territory of the Unitary State of the Republic of Indonesia who are born outside of a valid marriage according to religious law or belief in God Almighty , carried out based on a court order. 2) The legal consequences of the deed of recognition of illegitimate children made by a Notary, namely the deed of recognition of illegitimate children made by a notary has important legal consequences regarding legal proof, granting children's rights, official identity of children, legal obligations of children and legal protection to child. However, based on Presidential Decree Number 96 of 2018, the deed of recognizing a child made by a notary is not authentic because the notary does not have the authority to make a deed recognizing an illegitimate child because the determination is made based on a court order.